The structure of nuclear systems derived from low momentum nucleon–nucleon potentials - Kuckei, Jan (2003)
Various nuclear structure observables are evaluated employing low-momentum nucleon–nucleon (NN) potentials Vlow-k derived from the CD-Bonn and Nijmegen NN interactions VNN. By construction, the high momentum modes of the original VNN are integrated out in Vlow-k, with the requirement that the deuteron binding energy and low energy phase shifts of VNN are exactly reproduced. Using this interaction, we evaluate the bulk properties (binding energy and saturation density) of nuclear matter and finite nuclei, in particular their dependence on the cut-off parameter. We also study the pairing gap and the residual interaction in nuclear matter in terms of the Landau parametrization. At low and medium densities, the HF and BHF binding energies for nuclear matter calculated with the Vlow-k’s derived from the CD-Bonn and Nijmegen potentials are nearly identical. The pairing gaps and Landau parameters derived from Vlow-k are remarkably close to those given by the full-space VNN. The Vlow-k interactions, however, fail to reproduce the saturation property of nuclear matter at higher densities if the cut-off for the high momentum modes is assumed density independent.